Retroperitoneal robotic and laparoscopic surgery - Joseph, Jean V.; Patel, Hitendra (Springer, 2011)
Retroperitoneal Robotic and Laparoscopic Surgery provides urologists with an easy way to learn the extraperitoneal alternative when performing laparoscopic or robot assisted procedures. There are significant technical differences between intra-peritoneal and retroperitoneal surgery. There are occasions, particularly with a history of prior intra-abdominal surgeries, when the retroperitoneal route is not only less invasive, but provides an efficient and effective way of performing the operation. Retroperitoneal Robotic and Laparoscopic Surgery is a step-by-step guide of all extraperitoneal laparoscopic and robot assisted procedures. This book will support beginners in making the transition from open extraperitoneal to laparoscopic or robotic extraperitoneal procedures. It is also a valuable reference tool to further assist the intermediate and advanced laparoscopist to expand their skills working in the extraperitoneal space.